Planning a Waste Processing Site with the 3r Plus Principle in Kapur Village, Sungai Raya District, Kubu Raya Regency - Yenni Andriyani; Yulisa Fitrianingsih; Rizki Purnaini (Universitas Diponegoro, 2023)
Kapur Village is located in Sungai Raya District, Kubu Raya Regency. The existing condition of waste management has not been implemented properly due to the lack of waste management facilities, namely temporary waste disposal and other communal waste containers, so efforts are needed to handle the waste management system, by planning temporary waste disposal 3R plus. The aim of planning is to know, analyse existing condition of management waste, generation size, density, waste composition and planning the 3R temporary waste disposal design. The research method is sampling generation, density and composition of waste according to SNI-19-3964-1994, conducting interviews and questionnaires to obtain selected locations. The resulting waste generation is 0.35 kg/person/day. The density of domestic source waste is 142.09 kg/m3, while the largest density of non-domestic source waste is produced from restaurants at 113.32 kg/m3. The composition of domestic waste is dominated by organic waste with a percentage of 49.3%, while non-domestic waste is dominated by paper waste with a percentage of 30.60%. This 3R plus temporary waste disposal planning requires land of 1,112.3 m2. The planned waste management is is processing organic waste into composting using the hollow brick method, while inorganic waste in the form of plastics and bottles is processed into handicraft products.